Analisis Model Antrian Multi Channel-Single Phase Pada Doorsmeer Mobil dengan Menggunakan Software POM-QM for Windows - Rambe, Aida Zahrah Hasanati Br.; Rambe, Fatimah Zahra; Azzahra, Jihan; Gultom, Lidia Sartika; Chairunnisa, Putri (Lembaga Intelektual Muda (LIM) Maluku, 2024)
Queuing is the activity of a group of people or goods in a waiting line to wait for a service. The queueing system can be interpreted as the arrival of customers for a service, waiting to get service, and leaving the system after getting service. This research is applied research using the observation method. This research aims to provide solutions to queuing problems at Agung Auto Service car doorsmer Jl. S.M. Raja No. 3, Rantauprapat, North Sumatra. Data is taken by paying attention to the time of arrival of customers and how many customers can be served. This car doorman applies the First Come, First Served (FCFS) discipline, where the first customer to arrive will get the first service through the queuing process. Therefore, the model that can be used is the multi-channel single-phase model, where there are two or more service facilities flowed by a single queue. From the results of the calculation of the model simulation in POM-QM for Windows, it can be seen that the performance of the service system at the Agung Auto Service car doorsmeer is not optimal because initially there were only 3 service servers, causing queues. Therefore, it is necessary to add up to six service servers to produce optimal service